Answers from "the working actor" : two backstage columnists share ten years of advice - Apodaca, Jackie; Kostroff, Michael (Routledge, 2018)
For nearly a decade, Jackie Apodaca and Michael Kostroff shared duties as advice columnists for the actors' trade paper, Backstage. Their highly popular weekly feature, "The Working Actor," fielded questions from actors all over the country. A cross between "Dear Abby" and The Hollywood Reporter, their column was a fact-based, humorous, compassionate take on the questions actors most wanted answered. Using some of their most interesting, entertaining, and informative columns as launch points, Answers from "The Working Actor" guides readers through the ins and outs (and ups and downs) of the acting industry. Apodaca and Kostroff share an approach that is decidedly "on the ground." They've both labored in the trenches just like their readers-dealing with auditions, classes, photos, resumes, rehearsals, contract negotiations, representatives, jobs, challenging colleagues, and the search for that elusive life/career balance. There are few absolutes in the acting profession and virtually no proven and reliable steps. Unlike books that claim to offer "Quick Steps to a Successful Acting Career," Answers from "The Working Actor" deals honestly with the realities, providing facts, options, strategies, stories, points of view, and the wisdom of experience, while ultimately challenging readers to make their own decisions. This book will give new actors a head start on their journeys and remind experienced professionals that, in the acting business, there is never only one answer to any question